Relationship quality and its effects on college student’s psychological well-being - Rasyida, Afinnisa; Siregar, Maria Angelisa; Rachmah, Alifiah Nur'izza; Rachmawati, Raden Roro Fitria; Victor, Ivena Nathania; Hindrawan, Kezia Jeni (Intelektual Pustaka Media Utama, 2025)
The field of psychological well-being is extensively studied globally, encompassing positive relationships as a notable facet. Presently, there is a discourse emphasizing the need for research on relationships to encompass both positive and negative aspects, along with their effects on an individual’s overall well-being. The study aimed to identify the impacts of relationship qualities of three sources (parental, friendship, and romantic relationships) on college students’ psychological well-being. The 251 college students in Surabaya (Indonesia) and 139 college students in Hangzhou (China), selected using purposive sampling technique, were involved in this research. All participants have at least three social networks/sources of relationship, i.e., parents, best friends, and romantic partners. The network of relationships inventory -relationship quality version (NRI-RQV) was given to identify the qualities of relationship participants have from the three sources. Participants’ psychological well-being was observed using the PERMA-Profiler. Data was analyzed using Statistical Package for the Social Sciences (SPSS). In both countries, students highlight that the quality of the relationship between parents and college students has the most substantial influence on their psychological well-being, with parental approval being one of the key components. This finding provides valuable insights for developing an effective support system for college students.